2004
DOI: 10.2169/internalmedicine.43.982
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hypersensitivity Pneumonitis Caused by Aspergillus Complicated with Pulmonary Aspergilloma

Abstract: A 57-year-old man consulted our hospital with a history of the gradual onset of dyspnea and a productive cough. Chest computed tomographic (CT) scans showed a nodular shadow in a cavity lesion, and reticulonodular, cystic, and ground-grass opacities in the bilateral lung fields with honeycombing. He was diagnosed as having pulmonary aspergilloma and idiopathic pulmonary fibrosis (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…As CPA often arises in preformed cavities, it can also complicate other conditions which cause lung injury such as cryptococcosis and radiation therapy respectively . Furthermore, aspergilloma has been reported to be associated with chronic hypersensitivity pneumonitis …”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…As CPA often arises in preformed cavities, it can also complicate other conditions which cause lung injury such as cryptococcosis and radiation therapy respectively . Furthermore, aspergilloma has been reported to be associated with chronic hypersensitivity pneumonitis …”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
“…28,29 Furthermore, aspergilloma has been reported to be associated with chronic hypersensitivity pneumonitis. 30 According to the predisposing conditions, most cases of CPA occur in middle-aged patients, 5,7 but young CF patients 31,32 as well as younger adults, e.g. with history of tuberculosis 9 may be affected, too.…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Serological testing is used in the diagnosis of ABPA as well as invasive infection. Precipitating antibodies are typically present in ABPA and chronic cavitary pulmonary aspergillosis but not necessarily so during invasive infection of the immunosuppressed host [13]. On the other hand Aspergillus galactomannan antigen, a major component of the cell wall of Aspergillus, is detectable in the majority of cases of invasive pulmonary aspergillosis in those with underlying haematological disease and intensive care [14], and notably was also found in case 1 in high titre in a serum sample taken at the time of admission, consistent with (perhaps diagnostic of) invasive infection at this early time point.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, endogenous antigens associated with clinical infection may also induce HP. Y oshimoto et al [ 58 ] reported a case of HP precipitated by Aspergillus from an infectious aspergilloma, while S chreiber et al [ 59 ] described a case of HP caused by endogenous Candida albicans .…”
Section: Type Of Exposurementioning
confidence: 99%